Phenotypical Sub-setting of the First Episode of Severe Viral Respiratory Infection Based on Clinical Assessment and Underlying Airway Disease: A Pilot Study - Arroyo, Maria; Salka, Kyle; Perez, Geovanny F.; Rodríguez-Martínez, Carlos E.; Castro-Rodriguez, Jose A.; Gutierrez, Maria J.; Nino, Gustavo (Frontiers in Pediatrics, 2020)
Introduction: Viral bronchiolitis is a term often used to group all infants with the first episode of severe viral respiratory infection. However, this term encompasses a collection of different clinical and biological processes. We hypothesized that the first episode of severe viral respiratory infection in infants can be subset into clinical phenotypes with distinct outcomes and underlying airway disease patterns. Methods: We included children (≤2 years old) hospitalized for the first time due to PCR-confirmed viral respiratory infection. All cases were categorized based on primary manifestations (wheezing, sub-costal retractions and hypoxemia) into mild, hypoxemia or wheezing phenotypes. We characterized these phenotypes using lung-X-rays, respiratory outcomes and nasal protein levels of antiviral and type 2 cytokines (IFNγ, IL-10, IL-4, IL-13, IL-1β and TNFα). Results: A total of 50 young children comprising viral respiratory infection cases (n=41) and uninfected controls (n=9) were included. We found that 22% of viral respiratory infection cases were classified as mild (n=9), 39% as hypoxemia phenotype (n=16) and 39% as wheezing phenotype (n=16). Individuals in the hypoxemia phenotype had more lung opacities, higher probability of PICU admission and prolonged hospitalizations. Subjects in the wheezing phenotype had higher probability of recurrent sick visits. Nasal cytokine profiles showed that individuals with recurrent sick visits in the wheezing phenotype had increased nasal airway levels of type 2 cytokines (IL-13/IL-4). Conclusion: Clinically-based classification of the first episode of severe viral respiratory infection into mild, hypoxemia or wheezing phenotypes provides critical information about respiratory outcomes, lung disease patterns and underlying airway immunobiology.